A New Method for Winter Wheat Critical Nitrogen Curve Determination. (1st November 2013) - Chen, Pengfei; Zhu, Yunqiang
Abstract : As a plant‐based N diagnostic tool, critical N curves can be used to adjust the N input in a field according to the crop demand. Because the existing critical N curve determination methods may overestimate the critical N point, making the designed N curve above the actual one, this study presents an improved method to overcome this drawback. An N experiment was conducted during 2 yr (2010–2012) using different winter wheat ( Triticum aestivum L.) cultivars in the northwestern plain of Shandong Province, China. Shoot biomass and N concentration were sampled weekly during the growing season. A new method for designing critical N curves was developed based on the existing N curve determination method and the t ‐test inversion. Using the above data set, the new and existing methods for designing a critical N curve were compared, and the effects of the different cultivars on the proposed N curve were evaluated. The results showed that the critical N curves generated using existing methods can successfully classify N‐limited plants but fail to classify non‐N‐limited plants, however, the critical N curve determined using the new method was able to classify both N‐limited and non‐N‐limited plants satisfactorily. Cross‐validation showed that the new method exhibited a highest total correct classification rate of 76%, while the existing methods displayed total correct classification rates below 64%. Additionally, the proposed critical N curve is robust within species within the same region. Thus, the new method may be useful for N management in the field.